High Mountains Rising - Richard A. Straw, H. Tyler Blethen (University of Illinois Press, 2004)
In 1970, late in my undergraduate career at Ohio University in Athens, Ohio, I became involved with a group of students who were interested in learning more about the Appalachian region. Little did I know at that time that I was about to become part of an academic and cultural renaissance that would eventually result in my involvement in producing this introductory collection of essays on the history and culture of Appalachia. There is more than a little irony in how this came about. One of our projects was an attempt to add courses on Appalachia to the curriculum because Ohio University was located in the part of southeastern Ohio that had recently been included in the federal government’s new definition of Appalachia. I was a history major, so I volunteered to find a faculty member in the history department who might be interested in teaching such a class. I asked around, and it appeared that a good candidate might be the professor who taught courses on the American South. Like most undergraduates, I had not spoken often or at length with more than one or two of my teachers, and I did not know this man. I was somewhat intimidated, but I had volunteered and I believed in the idea we were pursuing, so I pressed on. One afternoon I found him in his office and asked whether he had a few minutes to talk. I introduced myself and told him that I was interested in Appalachia and that I had been attending meetings of a student group that was trying to raise awareness on campus of Appalachian issues. Eventually I asked him whether he thought that a course on the history of Appalachia was a good idea and whether he thought it might be possible. He listened politely but then said that what I proposed would be a problem because Appalachia has no history. I was stunned by his remarks; I left his office and did not recover for a long time from the embarrassment I felt from having asked his advice. At that time the only books about Appalachia I had read were Harry Caudill’s Night Comes to the Cumberlands and Jack Weller’s Yesterday’s People, but I was convinced that Appalachia, like every other region, people, or culture in the world, had a history. In one very real sense the book you now have in your hands is the culmination of that conversation more than thirty years ago. This is a book for anyone who is interested in learning more about the rich history and diverse cultures of Appalachia.